Symptomatic presentation of spontaneous pneumomediastinum in a young girl: a case report - Choubey, Abhinav; Choubey, Shivani (International Journal of Research in Medical Sciences, 2024)
Spontaneous pneumomediastinum (SPM) is a rare and typically benign condition that involves the presence of air in the mediastinum without an obvious cause, such as trauma or surgery. It most commonly affects adolescents and young adults, with a male predominance. This case report discusses a 14-year-old girl presenting with pleuritic chest pain and persistent cough, initially misdiagnosed as asthma exacerbation or lower respiratory tract infection. Despite multiple treatments, her symptoms persisted, and a high-resolution computed tomography (HRCT) scan eventually revealed pneumomediastinum. The patient was treated conservatively with analgesics and rest, and she experienced a complete resolution of symptoms within ten days. A review of the literature reveals that SPM is often self-limiting, with conservative management sufficient in most cases. While the condition mimics more serious diseases such as pneumothorax and pulmonary embolism, accurate diagnosis through imaging is key to avoiding unnecessary interventions. This report underscores the importance of considering SPM in young patients presenting with chest pain and respiratory symptoms, especially when they do not respond to standard treatments for more common conditions.